2013
DOI: 10.1063/1.4821817
|View full text |Cite
|
Sign up to set email alerts
|

An improved semiclassical theory of radical pair recombination reactions

Abstract: We present a practical semiclassical method for computing the electron spin dynamics of a radical in which the electron spin is hyperfine coupled to a large number of nuclear spins. This can be used to calculate the singlet and triplet survival probabilities and quantum yields of radical recombination reactions in the presence of magnetic fields. Our method differs from the early semiclassical theory of Schulten and Wolynes [J. Chem. Phys. 68, 3292 (1978)] in allowing each individual nuclear spin to precess ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 40 publications
2
70
0
Order By: Relevance
“…In fact, the initial electronic singlet state of the radical pair is quantum mechanically entangled [although the entanglement, as such, confers no advantage in terms of the general operation of the compass (60), nor is it essential for the existence of the spike]. We recently showed that the spin dynamics of long-lived radical pairs in weak magnetic fields can be described by a semiclassical approximation that becomes increasingly accurate as the number of nuclear spins is increased (61,62). If the behavior of a realistic radical pair magnetoreceptor can be satisfactorily modeled in terms of classical rather than quantum oscillations, then arguably it does not belong under the quantum biological umbrella.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the initial electronic singlet state of the radical pair is quantum mechanically entangled [although the entanglement, as such, confers no advantage in terms of the general operation of the compass (60), nor is it essential for the existence of the spike]. We recently showed that the spin dynamics of long-lived radical pairs in weak magnetic fields can be described by a semiclassical approximation that becomes increasingly accurate as the number of nuclear spins is increased (61,62). If the behavior of a realistic radical pair magnetoreceptor can be satisfactorily modeled in terms of classical rather than quantum oscillations, then arguably it does not belong under the quantum biological umbrella.…”
Section: Discussionmentioning
confidence: 99%
“…17 found that the process in Eq. (19) only occurs at temperatures below 200 K for PTZ-Ph n -PDI wires with n ≥ 2, whereas the experiments of Weiss et al 15 that we have compared with here were performed at room temperature. 16 Finally, the background could be due to a fraction of the radical pairs being formed in the triplet state, rather than the singlet state, during the initial charge separation:…”
Section: Background Contribution To the Triplet Yieldmentioning
confidence: 73%
“…It would be interesting if further experiments could be done to shed more light on the processes in Eqs. (17), (18), (19) and (22) in an attempt to resolve this issue. Especially since the need for a background correction to explain the high field behaviour of the triplet yield does not seem to be confined to these particular PTZ •+ -Ph n -PDI •− molecular wires: relative triplet yields Φ T (B)/Φ T (0) that are significantly larger than 1/3 in the high field limit have also been observed by Wasielewski and co-workers for a variety of other molecular wires.…”
Section: Background Contribution To the Triplet Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Although successful in some circumstances, 15 this approach conflicts with Newton's third law of motion, because the torque exerted on the electron spin by the nuclear spins is not balanced by an equal and opposite torque on the nuclear spins from the electron. Our recent extension to the SW theory 16 …”
Section: -14mentioning
confidence: 99%